Interlevel Connections as a Way to Increase the Ventilation Efficiency of a Mine Ventilation Network - a Case Study - Słota, Krzysztof; Słota, Zbigniew; Morcinek-Słota, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The exploitation of the deposit necessitates continuous optimisation of the ventilation network, as well as the need to change fans. One way of optimising the network and increasing the efficiency of ventilation may be to make interlevel connections in the form of large-diameter openings.
Keywords: mine ventilation; ventilation network control; ventilation network optimisation; ventilation efficiency